2018
DOI: 10.1186/s40537-018-0126-7
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting AIDS prevalence in the United States using online search traffic data

Abstract: Big Data, characterized by large volumes, high processing speed, and wide variety of datasets [1-3], have been shown to be very valuable in health care research, with Health Informatics being the field in which big data analytics have been extensively applied [4]. A popular way of addressing the challenge of Big Data is the analysis of online search traffic data [5, 6], mainly with data from Google Trends [7]. Over the past decade, this field of research, i.e., analyzing online search traffic data, has been wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 35 publications
2
29
0
1
Order By: Relevance
“…It is evident that the online interest in the term 'Chlamydia' is significant throughout the examined period, i.e., from 2004 to 2017. In the US, the top related searches for the term 'Chlamydia' from 2004 to 2016 include: 'chlamydia symptoms' (100), 'chlamydia gonorrhea' (50), 'symptoms of chlamydia' (38), 'chlamydia men' (36), 'std chlamydia' (34), 'std' (33), 'chlamydia treatment' (33), 'treatment chlamydia' (33), 'chlamydia in men' (28), 'chlamydia infection' (26), 'chlamydia in women' (25), 'what is chlamydia' (24), 'chlamydia test' (22), 'chlamydia symptoms women' (19), 'chlamydia symptoms men' (18), 'chlamydia symptoms in women' (16), 'chlamydia symptoms in men' (16), 'chlamydia discharge' (15), 'chlamydia signs' (14), 'chlamydia cure' (13). Table 1 consists of the Pearson correlation coefficients between Google Trends data on the term 'Chlamydia' and official Chlamydia cases in each US State from 2004 to 2016.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is evident that the online interest in the term 'Chlamydia' is significant throughout the examined period, i.e., from 2004 to 2017. In the US, the top related searches for the term 'Chlamydia' from 2004 to 2016 include: 'chlamydia symptoms' (100), 'chlamydia gonorrhea' (50), 'symptoms of chlamydia' (38), 'chlamydia men' (36), 'std chlamydia' (34), 'std' (33), 'chlamydia treatment' (33), 'treatment chlamydia' (33), 'chlamydia in men' (28), 'chlamydia infection' (26), 'chlamydia in women' (25), 'what is chlamydia' (24), 'chlamydia test' (22), 'chlamydia symptoms women' (19), 'chlamydia symptoms men' (18), 'chlamydia symptoms in women' (16), 'chlamydia symptoms in men' (16), 'chlamydia discharge' (15), 'chlamydia signs' (14), 'chlamydia cure' (13). Table 1 consists of the Pearson correlation coefficients between Google Trends data on the term 'Chlamydia' and official Chlamydia cases in each US State from 2004 to 2016.…”
Section: Resultsmentioning
confidence: 99%
“…This database contains data for 6 infectious diseases, i.e., HIV/AIDS, Chlamydia, Gonorrhea, Syphilis, Tuberculosis, and Hepatitis. Following the well performing forecasting results for AIDS [18], in this study we use data on the rest of the diseases included in AtlasPlus. The data retrieved for Hepatitis are from January 1st, 2004 to December 31st, 2015, while for the rest of the examined diseases; the examined time frame is from January 1st, 2004 to December 31st, 2016.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, a limitation of the tool is that it has been observed that data retrieved on different time points for the same time-frame may slightly vary. Despite the above, many studies in various subjects have shown that indeed Google data can be used to analyze or predict behavioral variations [4,5,8,13,16,23,26,[90][91][92] and that empirical relationships exist between online search traffic data and human behavior [93,94].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, a strength of Google search data is that it allows researchers to access data about controversial or sensitive topics that might not be as readily obtained in traditional methodologies such as survey research (Stephens-Davidowitz 2014). To date, researchers have analyzed Internet query data for a variety of topics, including: difficult to survey populations (Chykina and Crabtree 2018), social movements (Gross and Mann 2017), political behavior (Ma-Kellams et al 2017; Stephens-Davidowitz 2014), health-seeking behavior (Nuti et al 2014;Telfer and Obradovich 2017;Zhang et al 2018), consumer behavior (Goel et al 2010), weather and disaster related concerns (Sherman-Morris et al 2011), suicide surveillance (Ayers et al 2017;Gunn and Lester 2013;Hagihara et al 2012;Ma-Kellams et al 2016;Sueki 2011), AIDS (Mavragani and Ochoa 2018), pornography (Makin and Morczek 2015;Whitehead and Perry 2018), and illicit drug use (Gamma et al 2016). Internet searches provide an innovative way to learn about crime prevention.…”
Section: Introductionmentioning
confidence: 99%